If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying t(t + -26) = -160 Reorder the terms: t(-26 + t) = -160 (-26 * t + t * t) = -160 (-26t + t2) = -160 Solving -26t + t2 = -160 Solving for variable 't'. Reorder the terms: 160 + -26t + t2 = -160 + 160 Combine like terms: -160 + 160 = 0 160 + -26t + t2 = 0 Factor a trinomial. (10 + -1t)(16 + -1t) = 0Subproblem 1
Set the factor '(10 + -1t)' equal to zero and attempt to solve: Simplifying 10 + -1t = 0 Solving 10 + -1t = 0 Move all terms containing t to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -1t = 0 + -10 Combine like terms: 10 + -10 = 0 0 + -1t = 0 + -10 -1t = 0 + -10 Combine like terms: 0 + -10 = -10 -1t = -10 Divide each side by '-1'. t = 10 Simplifying t = 10Subproblem 2
Set the factor '(16 + -1t)' equal to zero and attempt to solve: Simplifying 16 + -1t = 0 Solving 16 + -1t = 0 Move all terms containing t to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + -1t = 0 + -16 Combine like terms: 16 + -16 = 0 0 + -1t = 0 + -16 -1t = 0 + -16 Combine like terms: 0 + -16 = -16 -1t = -16 Divide each side by '-1'. t = 16 Simplifying t = 16Solution
t = {10, 16}
| 9-c= | | 2x+18=15x-12 | | (2x+4y+2-8)+(8x-3y-2+9)+(-3x+y-2z-2)= | | 4n+32=8n+14 | | -(x-4)=-24 | | x=2+2.5y | | 2(x+7)=3(3-x)+8 | | 2=5+15k | | 0.75(3x+2)=2(3-4x)+16 | | 9m-15=-50+2m | | 5-5y=10 | | .3333(4x+5)+-.555(8x-4)=20 | | 0.1111(x+9)=.037037(3x+27) | | -0.75n+1=-11 | | 3(x+7)= | | 3y-18=9+6y | | -(3xy-12)+3(3xy+6)= | | -7(-x+4)+10(-x)+3(-4x-4)+40= | | 4+(a-2)=(a+3)-(a+1) | | 6(x+5)-1=34-4x-5+10x | | 8h-4=16 | | -2(2x-7)+7=-4x+21 | | x^2+10000x+24993728=0 | | 2+8(m-6)= | | 10-x+32= | | 7x^4=3584x | | 6x+4=6(x+6) | | 4x-3/5=2/5 | | 15y^2+8y+1= | | x+1+2x=5x-7 | | -2y-23=6y+17 | | -3+9(x-1)=17x+5-8x |